Consumo de ceftriaxona en el servicio de neurología del hospital nacional almanzor aguinaga asenjo (hnaaa) essalud chiclayo 2009 - Chávez Cancino, Carla Elizabeth (2010)
This report was aimed to determine the consumption of ceftriaxone in the service of Almanzor Aguinaga Asenjo Neurology Chiclayo EsSalud-2009 National Hospital, to analyze the trend and statistical significance in the use of ceftriaxone. The data were obtained from the computer records of Hospital Management System hospital. The study population consisted of patients hospitalized in the Neurology to which were prescribed ceftriaxone in 2009. The average annual consumption of ceftriaxone expressed in DDD / 100camas / day in the service of Neurology is 34.32 . The consumption trend in this service do not show statistical significance, and therefore does not increase consumption tends not to decrease over time. The total cost in 2009 of ceftriaxone is 6258.26 nuevos soles.